FORMULA 1 DOCUMENTARY SERIES: THE DRIVE TO SURVIVE AS HYPERREALITY - Isara Sondang Ranggapuri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research explores the construction of hyperreality in the Formula 1: Drive to Survive documentary series produced by Netflix, focusing on Season 6 released in 2024. Using Jean Baudrillard's theory of hyperreality and Pierre Bourdieu’s concepts of cultural and symbolic capital, the study analyzes how the documentary reconstructs the world of Formula 1 into a dramatized narrative that transcends the original sporting context. Employing a qualitative approach with a text analysis strategy, the research examines the visual and narrative content of each episode to uncover the representations, emphases, and meanings formed through media framing. Findings indicate that the series no longer serves to accurately represent the real dynamics of Formula 1, such as teamwork, technical complexity, and racing strategy. Instead, it constructs an entertainment-driven hyperreality that simplifies the drivers into fictionalized roles of protagonists and antagonists, emphasizing interpersonal drama and emotional spectacle. This hyperreal portrayal aligns with the interests of capitalist media in commodifying sports content for mass consumption. The study highlights the implications of such media constructions on public perception and contributes to the discourse on postmodern media, representation, and cultural production.